The First Men in the Moon - Wells, H. G.; Edited and Notes by James, Simon J. (New York Oxford University Press, 2017)
At the village of Lympne, on the south coast of England, the failed playwright Mr Bedford meets the brilliant inventor Mr Cavor, and together they invade the moon. The First Men in the Moon is an inspired and imaginative fantasy of space travel and alien life, a satire of turn-of-the-century Britain
Keywords: Space flight to the moon -- Imperialism -- Science fiction